Pushing the Speed of Assistive Technologies for Reading. Issue 1 (7th December 2018) - Schneps, Matthew H.; Chen, Chen; Pomplun, Marc; Wang, Jiahui; Crosby, Anne D.; Kent, Kevin
ABSTRACT: People who are practiced in using text‐to‐speech can drive listening speeds to surprisingly high limits. Here, we investigate the extent to which people who are otherwise untrained, with and without dyslexia, can increase their reading speed when forcibly accelerated visual or auditory presentations are used in isolation or in tandem. The experiment examined the reading speed and comprehension of 43 college students using three methods enabled by software on a handheld device: forcibly accelerated visual augmentation, auditory text‐to‐speech, and a combination of the two. We found that both typical and impaired readers attained the highest reading speed using the combined method, controlling for comprehension. Importantly, those with dyslexia using the combined methods reached the equivalent reading speed of typical readers using paper, visual, or auditory methods, with no loss in comprehension. Findings here suggest that in future evolutions—using technologies available today—parallel neurological pathways for language processing can be exploited to optimize reading for those impaired.